A comparative study of virtual hand prosthesis control using an inductive tongue control system. Issue 1 (2nd January 2016) - Johansen, Daniel; Sebelius, Fredrik; Jensen, Stig; Bentsen, Bo; Popović, Dejan B.; Andreasen Struijk, Lotte N. S.
ABSTRACT: This study compares the time required to activate a grasp or function of a hand prosthesis when using an electromyogram (EMG) based control scheme and when using a control scheme combining EMG and control signals from an inductive tongue control system (ITCS). Using a cross-over study design, 10 able-bodied subjects used a computer model of a hand and completed simulated grasping exercises. The time required to activate grasps was recorded and analyzed for both control schemes. End session mean activation times (ATs; seconds) for the EMG control scheme grasps 1 -5 were 0.80, 1.51, 1.95, 2.93, and 3.42; for the ITCS control scheme grasps 1 ‒5 they were 1.19, 1.89, 1.75, 2.26, and 1.80. Mean AT for grasps 1 and 2 was statistically significant in favor of the EMG control scheme ( p = 0.030; p = 0.004). For grasp 3 no statistical significance occurred, and for grasps 4 and 5 there was a statistical significance in favour of the ITCS control scheme ( p = 0.048; p = 0.004). Based on the amount of training and the achieved level of performance, it is concluded that the proposed ITCS control scheme can be used as a means of enhancing prosthesis control.